Investigation of the Optimal Output Parameter Equation in a Small Ethanol-Fueled Engine - Khoa, Nguyen Xuan; Hung, Chu Duc; Vinh, Nguyen Thanh; Chuc, Le Huu; Han, Nguyen Tien (Engineering, Technology & Applied Science Research, 2025)
Biofuels are increasingly recognized as an urgent solution to reducing engine emissions and achieving sustainable development goals. Among them, ethanol fuel stands out as a promising candidate due to its clean combustion properties and high energy regeneration potential. This study investigates the optimal equations for the engine output parameters to enhance power and improve the overall engine performance. The findings demonstrate that optimizing the ignition angle allows the engine to achieve a higher power output, significantly reduce the fuel consumption, and minimize the emissions of harmful pollutants, such as CO, NOx, and HC. This research provides a solid foundation for the application of ethanol as a viable alternative fuel in internal combustion engines, paving the way for cleaner and more environmentally friendly engine technologies that meet stringent emission standards. Furthermore, the derived equations and insights offer practical implications for improving the existing engine systems and guiding the development of advanced biofuel-powered engines for future applications.